Myles Standish Adventurous Boy - Stevenson, Augusta (the Bobbs-Merrill Company New York, 1962)
The boyhood of the Englishman, a Separatist, who helped the Pilgrims establish the first English colony in America, at Plymouth.
Keywords: Standish, Myles -- 1584?-1656